O ensino-aprendizagem da língua portuguesa no curso normal superior, na modalidade de educação a distância : da teoria à transposição didática - Rocha, Silvana Soares Siqueira (2012)
Teacher training has been one of the most discussed fields of educational knowledge in texts and educational practices during the last years. This thesis presents the results of researches conducted in the project "Ensino-aprendizagem de língua materna: da teoria à transposição didática". It approaches, through an action research, Portuguese language teaching and teacher training of the Curso Normal Superior in distance education. This study aims to analyze the didactic transposition focused on the formulation of didactic material used during the supervised practice of the subjects of Language. It also aims to offer a reformulation. The theory agrees with the theoretical and practical considerations that are interconnected with the process from production to reception of the pedagogical material by trainee teachers from the perspective of philosophical principles of Interactionism in the context of Applied Linguistics. The qualitative/interpretive research provides clear results that difficulties present in distance education course are very similar to the ones in classroom education since the brief contact with trainee teachers occurs in both modalities. Due to this scenario, it is emphasized that despite the progress there is still so much to be done in the field of research and thought. This is necessary to a didactic transposition which really covers the function of understanding the theories in order to have a more efficient educational practice and also the improvement ofPortuguese language learning and teaching. Such responsibility in the context of distance education involves the commitment of many professionals, among them the presence tutor who plays a fundamental role since his or her function is to work as a training co-supervisor.